Expenditure Incurred by Patients of Pulmonary and Extrapulmonary Tuberculosis Under Revised National Tuberculosis Control Programme in District Tuberculosis Center, Jammu - Anuradha Kalotra; Dinesh Kumar; Ravi Kumar; Arvind Kumar yadav; Kiran Lachala; Bhavna Sahni (Medsci Publications, 2023)
Background: Tuberculosis (TB) patients suffer enormously due to huge cost on diagnosis and treatment. This study aims to assess the total expenditure and its predictors among patients of TB. Methodology: A longitudinal study was conducted among TB Patients registered in first quarter of 2018 at District Tuberculosis Center, Jammu. Data was collected by interviewing the patients and their attendants. Statistical significance of median expenditure between patients of pulmonary and extrapulmonary TB in relation to various predictors was assessed using nonparametric tests followed by Multiple Linear Regression. Results: Total median cost, median direct and indirect cost incurred by a TB patient were recorded as USD 489.55, USD 246.55 and USD 229.5 respectively. Treatment costs were slightly higher in patients of pulmonary TB in comparison to extrapulmonary TB (p>0.05). On bivariate analysis, upper class, previously treated patients, Category 2 patients, with chronic illnesses, with guardians and who were employed expended significantly higher amounts on their treatment, but on multivariate analysis, only formal employment, current earning and being reimbursed significantly predicted the total cost (p < .001, adjusted R square = 0.56). Conclusion: Huge direct costs incurred by patients is a matter of great concern, more so as the Indian government has made all diagnostics and treatment free since the inception of the RNTCP.